RELATIONSHIP OF CHARACTERISTICS AND KNOWLEDGE LEVELS WITH NUTRITIONAL PRACTICES IN PREGNANT WOMEN IN THIRD TRIMESTER - Ana Nata Tanjung S. Ruing; Regina Vidya Trias Novita; Ainum Jhariah Hidayah Jhariah Hidayah (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2021)
Knowledge of healthy food consumption, especially protein intake during pregnancy, is very important for pregnant women, because it can influence the attitudes and behavior of pregnant women in consuming daily food which can affect the incidence of complications during pregnancy. The aim of this study was to determine the relationship between maternal characteristics and knowledge levels with the practice of balanced nutrition consumption at the Nagi Larantuka Health Center, East Flores. This study asa a quantitative method with a cross-sectional design. The research sample was pregnant women in the 3rd trimester with a total sample of 137 respondents. The data collection tool with a questionnaire that has been tested for validity and reliability. Data analysis used the Chi-Square. The results showed that 56.2% mothers with good knowledge. There was a significant relationship between age (0.000), education (0.000), and knowledge (0.023) with the practice of consuming balanced nutrition, but there is no significant relationship between pregnancy with the practice of consuming balanced nutrition which has (p value 0.801). The suggestions for the practice of balanced nutrition consumption for pregnant women in thrid trimester, needed require cross-sectoral collaboration implementation between health workers and cadre as a recommendation for future research.